The role of institutional trust in the adoption of gold dinar in Kelantan: an empirical analysis - Adewale, Abideen Adeyemi; Owolabi Yusuf, Muhammad-Bashir; Mydin Meera, Ahamed Kameel; Mat Ghani, Gairuzazmi; Abdul Manap, Turkhan Ali (Asian Network for Scientific Information, 2012)
The August 2007 global financial crisis has been linked to the fiat monetary system. This has made the world political leaders to call for the rebuild of the world monetary system from the scratch as was done at Breton Wood. One of the suggested options is the adoption of an alternative monetary system based on gold. In these regard, some states in Malaysia, for example, Kelantan have taken the initiative to mint their own gold dinar to be used simultaneously with the fiat money (Malaysian Ringgit). An unexplored issue in this regard is the rationale for adoption of such alternative mean of exchange. As such, this study adopts an extended theory of planned behavior (TPB) in which h u t is included as an antecedent variable in the original TPB model. Structural equation modeling analysis was carried out on data elicited from economic active residents in Kelantan via survey questionnaire. This is to assess the indirect relative explanatory strength of h u t on adoption of gold dinar in Kelantan using attitude, social norms and perceived behavioral control as mediators. The study found that the structural model fits the data. Also, h u t was found to influence adoption of the gold dinar while attitude and perceived behavioral control mediates the relationship.